Analisis Kesesuaian Kawasan Perairan Pulau Bungin untuk Ekowisata Snorkeling di Kecamatan Tambelan Kabupaten Bintan (Suitability Analysis of Bungin Island Aquatic Area for Snorkeling Ecotourism in Tambelan District, Bintan Regency) - Karnanda Karnanda; Febrianti Lestari; Dedy Kurniawan (Program Studi Manajemen Sumber Daya Perairan, 2019)
The suitability research of Bungin Island for snorkeling ecotourism in Tambelan Subdistrict aims to determine suitability of the Bungin Island area for snorkeling ecotourism. The methods was used to determine the stations for data collection in this area using purposive sampling method based on the location of coral. Results of the research parameters taken from each station were as follows: (1) coral cover at station 1 is 48% or conditional according to snorkeling ecotourism as well as at station 2 and station 3 which is 69% and 65.6% which means suitable for snorkeling ecotourism , (2) the water brightness in each station is 100%, (3) the total types of coral life forms obtained by each station are 12 species which are dominated by coral massive and acropora branching, (4) total species of reef fish are 57 species of reef fish that is 56 types at station 1, 51 types at station 2 and 52 types at station 3, (5) current speed ranges obtained at each station ranging from 9.51-14.02 cm / second, (6) as for the range of depth levels of each 1.6-2.0 meter station, (7) the width of the reef stretch in the north of the island ranges from 51.3 to 113 meters (8) accessibility is classified as S3 according to conditional, based on the suitability index of Bungin Island ecotourism area suitable for ecow say snorkeling.